Ankle Fractures: The Current State of Online Patient Information. Issue 4 (August 2021) - Noback, Peter C.; Trupia, Evan P.; Dziesinski, Lucas K.; Sarpong, Nana O.; Trofa, David P.; Vosseller, J. Turner
Background. We assessed the quality, accuracy, and readability of websites for ankle fractures. Methods. Ankle Fracture, Broken Ankle, and Fibular Fracture were entered into 3 search engines. The first 25 results from each search were collected. Quality, accuracy, and readability were assessed by a custom rubric, 3 surgeons, and Fleisch-Kincaid grade level (FKGL), respectively. Results. A total of 57 websites were included: 24 were assigned to Ankle Fracture, 26 to Broken Ankle, and 7 to Fibular Fracture. The average quality score out of 36, accuracy score out of 12, and FKGL for all websites were 13.1 ± 6.8, 10.8 ± 1.2, and 9.6 ± 1.7, respectively. Websites assigned to the term Broken Ankle had a significantly lower New Dale-Chall score. Websites of lower FKGL and appearing earlier in results had significantly higher quality scores. Physician specialty societies (PSSs) had a significantly lower FKGL than websites of other types. Conclusion. The readability of patient materials is above the recommended level for ankle fractures. Encouragingly, a trade-off between readability and quality was not found. Patients should use search terms they are familiar with and prioritize websites that appear earlier in search results, are easier to read, and produced by PSSs. Level of Evidence : Level 3